Plausible Scenarios for Thai Energy Businesses in the Next 30 Years - Nakapreecha, N.; Pongthanaisawan, J.; Wangjiraniran, W. (Frontiers in Energy Research, 2021)
The energy sector is currently facing different challenges. It is necessary for business leaders to understand the forthcoming changes that will affect their businesses in order to prepare themselves for any uncertainties and take advantage of new opportunities. This paper identifies changes that are expected to have an impact on Thailand’s energy system in the next 30 years and explores plausible scenarios for Thailand’s energy sector under such changes. The study starts with an examination of global and local circumstances. The examination pinpoints a focal issue as “to achieve sustainable development goals (SDG) by 2050”. Then, STEEP analysis is implemented to identify business drivers in social (S), technological (T), economical (E), ecological (E), and political (P) aspects. Subsequently, consultations with stakeholders are arranged to finalize the critical uncertainties. Policy and technology are found to be two of the most powerful factors affecting energy business and are, therefore, used as fundamental frameworks for scenario development. Accordingly, four plausible scenarios are derived providing different possible prospects for Thailand’s energy businesses. The findings can further be used in the analysis of national energy balance with detailed sector-by-sector projections. All of which will be beneficial in strategic energy planning at both the national and corporate level with a view to achieving the SDGs by 2050.